Equivalent Mathematical Programming Models of Pure Capital Rationing - Bradley, Stephen P.; Frey, Sherwood C. (Journal of Financial and Quantitative Analysis, 1978)
Stephen P. Bradley, Sherwood C. Frey, Jr., Equivalent Mathematical Programming Models of Pure Capital Rationing, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 2 (Jun., 1978), pp. 345-361